Construction of Abraham Maslow's Thought in The Perspective of Maqashid Sharia - Miftachul Ulum; Abdul Mun’im (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2023)
Humans cannot be understood as mere physical objects. Humans were created nothing but to worship Allah. Abraham Maslow's thought that humans are only in the form of material elements that are only fulfilled by fulfilling physical needs. The purpose of this study is to examine the levels of needs according to Abraham Maslow in maqasid sharia. The concept of maqasid sharia places religion as a benchmark in order to save human souls. The levels of need in the sharia maqasid concept include hifdz addin (preservation of religion), hifdz al nafs (preservation of the soul), hifdz al mal (preservation of property), hifdz aql (preservation of reason), and hifdz al nasl (preservation of offspring). Abraham Maslow stated that someone who has achieved self-actualization is universal, will be able to uphold the values ​​of goodness in dealing with others even though it is not religious. The concept of maqasid sharia views the achievement of human self-actualization as humans will tend to be more obedient to God and always do good to others.